PENGARUH E-SERVICE QUALITY TERHADAP KEPUTUSAN PEMBELIAN MELALUI E-TRUST SEBAGAI VARIABEL MEDIASI (Studi pada Pengguna Situs BukaLapak di Kota Semarang ) - Dina Setyowati; Sri Suryoko (Jurnal Ilmu Administrasi Bisnis, 2020)
The rapid development of technology makes business competition in the e-commerce increasingly stringent. Consumer purchasing decision making is influenced by several factors, one of which is psychological factors (service quality and trust). BukaLapak is one of the Indonesian companies engaged in e-commerce. The problem with this research is the large number of newcomers that causes consumers to compare e-service quality and e-trust in BukaLapak with other e-commerce. This study aims to study the effect of service quality on purchasing decisions through trust in sites in Semarang. This type of research used is descriptive method with quantitative research. The population of this research is Semarang City residents who use BukaLapak site, taken as a sample of 100 people. The technique of collecting data using online and offline questionnaires, documents, and literature studies. The sampling technique used in this study was purposive sampling. The analysis technique used is conversion analysis, simple regression analysis, multiple regression analysis, coefficient of determination test, t test, f test, normality test, and sobel test with the help of the IBM SPSS program (Product Solutions and Statistical Services) version 21.0. Based on the results of the analysis can conclude a positive and significant effect between e-service quality and trust in purchasing decisions, as well as trust variables can mediate between service quality variables on purchase outcomes. While the suggestion for BukaLapak is the repair feature that will be used on the site, and site enhancements to improve BukaLapak site access.